KRITIK SOSIAL PADA LAGU-LAGU NAVICULA DALAM ALBUM SALTO KAJIAN: SOSIOLOGI SASTRA - Laurensius Hendro Januandi Sani; Henricus Henricus; Indayani Indayani (Buana Bastra, 2018)
His study aimed to describe social problems and forms of social criticism delivery in Navicula songs in the album "salto" .Sumber research data is the song's lyrics in the albumNavicula "salto. The study focused on issues relating to social criticism that examined in thesociology of literature, especially the works of sociology sastra.Data obtained by reading andrecording techniques. qualitative data. The validity of the data obtained through the validityand reliability of data.The results showed the following matters: first, social criticism whatever is on Navicula songs in the album "salto" include; (A) poverty, (b) the problem of evil, (c) familyproblems, (d) the population problem, (e) environmental problems, (f) religious issues, (g) thebureaucracy. Both Navicula lyrics in the album "salto" contains a lot of social criticism canbe used as learning materials for the words used is easily understood and can be applied inteaching literature, especially in discussing the lyrics of the song.